Augmented renal clearance in critically ill patients: etiology, definition and implications for beta-lactam dose optimization. (October 2015) - Sime, Fekade Bruck; Udy, Andrew A; Roberts, Jason A
Highlights: Augmented renal clearance (ARC) is a prevalent condition in the critically ill. ARC may result in sub-therapeutic exposure of renally eliminated antibiotics. Beta-lactams are particularly affected due to their pharmacokinetic and pharmacodynamic characteristics. Dose optimization is necessary to circumvent the influence of ARC. Therapeutic drug monitoring may be necessary to guide dose optimization. Abstract : The renal clearance of antibiotics may be elevated in some critically ill patients. This paper reviews this recently described phenomenon, referred to as augmented renal clearance (ARC). ARC is considered to be driven by pathophysiological elevation of glomerular filtration, and is defined as a creatinine clearance >130 mL/min/173 m 2 . This in turn promotes very low antibiotic concentrations. This effect may lead to adverse clinical outcomes, particularly with beta-lactam antibiotics, as they require prolonged exposure for optimal antibacterial activity. The use of extended or continuous infusions is an effective strategy to improve exposure. However, because the effect of ARC is potentially quite variable, regular therapeutic drug monitoring (TDM) may be necessary to ensure all patients achieve effective concentrations.